2014
DOI: 10.1002/elps.201300438
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic high‐resolution computer simulation of isotachophoretic enantiomer separation and zone stability

Abstract: The development of electrophoretic computer models and their use for simulation of electrophoretic processes has increased significantly during the last few years. Recently, GENTRANS and SIMUL5 were extended with algorithms that describe chemical equilibria between solutes and a buffer additive in a fast 1:1 interaction process, an approach that enables simulation of the electrophoretic separation of enantiomers. For acidic cationic systems with sodium and H3 0(+) as leading and terminating components, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…For the studied example, no migration order inversion is predicted and CEC separations are shown to be quicker and electrophoretic displacement rate reduced in comparison to that in free solution. Dynamic computer simulation also provides insight into analyte stacking across conductivity and buffer additive gradients, changes of additive concentration, buffer component concentration, pH and conductivity across migrating sample zones and peaks, zone dispersion under electrokinetic conditions, and the formation and migration of system peaks as was discussed in previous publications . For example, simulation data revealed that separations of cationic enantiomers in phosphate buffers at low pH occur behind a fast cationic migrating system peak that has a small impact on the buffer composition under which enantiomeric separation takes place .…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…For the studied example, no migration order inversion is predicted and CEC separations are shown to be quicker and electrophoretic displacement rate reduced in comparison to that in free solution. Dynamic computer simulation also provides insight into analyte stacking across conductivity and buffer additive gradients, changes of additive concentration, buffer component concentration, pH and conductivity across migrating sample zones and peaks, zone dispersion under electrokinetic conditions, and the formation and migration of system peaks as was discussed in previous publications . For example, simulation data revealed that separations of cationic enantiomers in phosphate buffers at low pH occur behind a fast cationic migrating system peak that has a small impact on the buffer composition under which enantiomeric separation takes place .…”
Section: Discussionmentioning
confidence: 83%
“…Dynamic computer simulation of electrophoretic processes provides component distributions and profiles of the column properties as function of electrophoresis time . The separation of ketoconazole enantiomers in presence of OHP‐β‐CD was first investigated using SIMUL5complex with three concentrations of the chiral selector together with the input data presented in Table (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The two models were found to properly describe the migration behavior of enantiomers, dynamics of chiral separations, and formation of system peaks in free solution via use of complexation constants and specific mobilities of analyte–selector complexes . Dynamic simulation revealed zone dispersion due to complexation that can particularly occur at low concentration of a chiral selector and high complexation constants ; migration order reversal that can occur by changing the chiral selector or for a given selector by varying pH of the BGE or, at constant pH, the CD concentration ; occurrence and migration of system peaks ; and isotachophoretic enantiomer separation and zone stability . The same simulators can also be employed to characterize the impact of complexation on the buffer and peak properties in the case of an interaction between the selector and one or several buffer components .…”
Section: Introductionmentioning
confidence: 99%